Thylakoid Membrane Remodeling during State Transitions in Arabidopsis - Chuartzman, Silvia G. (American Society of Plant Biologists, 2008)
Adaptability of oxygenic photosynthetic organisms to fluctuations in light spectral composition and intensity is conferred by state transitions, short-term regulatory processes that enable the photosynthetic apparatus to rapidly adjust to variations in light quality. In green algae and higher plants, these processes are accompanied by reversible structural rearrangements in the thylakoid membranes. We studied these structural changes in the thylakoid membranes of Arabidopsis thaliana chloroplasts using atomic force microscopy, scanning and transmission electron microscopy, and confocal imaging. Based on our results and on the recently determined three-dimensional structure of higher-plant thylakoids trapped in one of the two major light-adapted states, we propose a model for the transitions in membrane architecture. The model suggests that reorganization of the membranes involves fission and fusion events that occur at the interface between the appressed (granal) and nonappressed (stroma lamellar) domains of the thylakoid membranes. Vertical and lateral displacements of the grana layers presumably follow these localized events, eventually leading to macroscopic rearrangements of the entire membrane network.